Multimodal correlative imaging and modelling of phosphorus uptake from soil by hyphae of mycorrhizal fungi. Issue 2 (15th February 2022) - Keyes, Sam; van Veelen, Arjen; McKay Fletcher, Dan; Scotson, Callum; Koebernick, Nico; Petroselli, Chiara; Williams, Katherine; Ruiz, Siul; Cooper, Laura; Mayon, Robbie; Duncan, Simon; Dumont, Marc; et al.
Summary: Phosphorus (P) is essential for plant growth. Arbuscular mycorrhizal fungi (AMF) aid its uptake by acquiring P from sources distant from roots in return for carbon. Little is known about how AMF colonise soil pore‐space, and models of AMF‐enhanced P‐uptake are poorly validated. We used synchrotron X‐ray computed tomography to visualize mycorrhizas in soil and synchrotron X‐ray fluorescence/X‐ray absorption near edge structure (XRF/XANES) elemental mapping for P, sulphur (S) and aluminium (Al) in combination with modelling. We found that AMF inoculation had a suppressive effect on colonisation by other soil fungi and identified differences in structure and growth rate between hyphae of AMF and nonmycorrhizal fungi. Our results showed that AMF co‐locate with areas of high P and low Al, and preferentially associate with organic‐type P species over Al‐rich inorganic P. We discovered that AMF avoid Al‐rich areas as a source of P. Sulphur‐rich regions were found to be correlated with higher hyphal density and an increased organic‐associated P‐pool, whilst oxidized S‐species were found close to AMF hyphae. Increased S oxidation close to AMF suggested the observed changes were microbiome‐related. Our experimentally‐validated model led to an estimate of P‐uptake by AMF hyphae that is an order of magnitude lower than rates previously estimated – a result with significant implications for the modelling of plant–soil–AMF interactions.